Kinerja Dinamis Kendaraan Toyota Avanza Tipe G Tahun 2011 - Ardiansyach Putra, Ferdioan; Setyo Pamuji, Didit; Harianto; Abdulkadir (ReTII, 2022)
This study aims to analyze the dynamic performance of the 2011 Toyota Avanza Type G, which includes engine performance, maximum speed, time required to reach maximum speed, climbability and steering system performance. The analysis is based on empirical equations from the existing literature and vehicle specifications. From the analysis results obtained engine performance characteristics, the maximum speed that can be achieved is 165.6 km / h, the time required to reach a maximum speed of 24.87 seconds, able to climb at a maximum slope angle of 50.99Â° using 1st gear, able to turn with a turning angle (Î´i) to 40Â° without slipping.